Kajian Akhlak Rasulullah dalam Meningkatkan Kinerja Entitas Bisnis pada CV. Sulawesi Herba Nusantara di Kabupaten Soppeng - Abd. Muzakkir; Lince Bulutoding; Abdul Wahid Haddade (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine how the study of the morals of the prophet Muhammad. In improving the performance of Islamic business entities on CV. Sulawesi Herba Nusantara in Soppeng Regency. This type of research is qualitative using a theological-normative, phenomenological and Islamic economic approach. The results showed that CV. Sulawesi Herba Nusantara has four performances, namely; material performance, mental performance, spiritual performance, and fraternity performance. The morality of the Messenger of Allah. in improving company performance, namely: Shiddiq: constructing the value of admitting mistakes, being responsible, and committed, having an impact on material performance. Tabligh: constructing the value of discussing together, solving problems in a good way, and criticism and suggestions as a means of evaluation, has an impact on mental performance. Amanah: constructs the value of responsibility and trust, has an impact on mental performance. Fathanah: constructing spirituality through the value of a good attitude, being educated and performing prayers, has an impact on spiritual performance. Al-samahah: constructing the value of deliberation related to mental performance and Islamic philanthropic values ​​and creating jobs, having an impact on the performance of brotherhood. The implication of this research is to make business entities aware of the importance of applying the morals of the Prophet Muhammad in their operation.